Diffuse Alveolar Damage: A Common Phenomenon in Progressive Interstitial Lung Disorders - Kaarteenaho, Riitta; Kinnula, Vuokko L. (Pulmonary Medicine, 2011)
It has become obvious that several interstitial lung diseases, and even viral lung infections, can progress rapidly, and exhibit similar features in their lung morphology. The final histopathological feature, common in these lung disorders, is diffuse alveolar damage (DAD). The histopathology of DAD is considered to represent end stage phenomenon in acutely behaving interstitial pneumonias, such as acute interstitial pneumonia (AIP) and acute exacerbations of idiopathic pulmonary fibrosis (IPF). Acute worsening and DAD may occur also in patients with nonspecific interstitial pneumonias (NSIPs), and even in severe viral lung infections where there is DAD histopathology in the lung. A better understanding of the mechanisms underlying the DAD reaction is needed to clarify the treatment for these serious lung diseases. There is an urgent need for international efforts for studying DAD-associated lung diseases, since the prognosis of these patients has been and is still dismal.